CBPWM and SVPWM equivalent relationship on single‐phase NPC N‐level inverters with arbitrary sequence. Issue 17 (22nd January 2021) - He, Yingjie; Liu, Yunfeng; Lei, Chao; Cheng, Ruiqi; Liu, Jinjun
Abstract : Single‐phase multilevel neutral‐point‐clamped (NPC) voltage source inverter has been widely applied in AC traction drive system, the carrier‐based pulse width modulation (CBPWM) method and the space vector pulse width modulation (SVPWM) method are mainly two modulation methods for single‐phase NPC multilevel converters, and there is a certain relationship between these two modulation strategies. In this study, the unified relationship between SVPWM and CBPWM in single‐phase three‐level and five‐level NPC has been analysed. Then by injecting the zero‐sequence component into the initial modulation wave, the same switching state and output current as SVPWM can be achieved through modulation waves decomposed under the CBPWM strategy. Finally, the unified theory of SVPWM and CBPWM in an N ‐level inverter with an arbitrary number of segments sequence was deduced. The simulation and experimental results illustrate that the unified theory between CBPWM and SVPWM is correct. With the zero‐sequence injected, CBPWM can realise the same effect as SVPWM, but the former is simpler than the latter, which is easy to promote for higher‐level applications.